The Relationship Between Fluid Restriction Compliance and Hypervolemia in Chronic Kidney Failure Patients Undergoing Hemodialysis at RSD Gunung Jati Cirebon City - Kasmad; Septiyadi, Riko; Mulyati, Lia (INDOGENIUS, 2025)
Background & Objective: Chronic kidney disease (CKD) leads to progressive loss of renal function requiring hemodialysis as a substitute therapy. Compliance with fluid restriction is crucial to prevent fluid overload (hypervolemia) which can cause complications such as pulmonary edema and hypertension. This study aims to analyze the relationship between fluid restriction compliance and hypervolemia occurrence in CKD patients undergoing hemodialysis at RSD Gunung Jati Cirebon. Method:. A descriptive correlational study with a cross-sectional approach was conducted on 98 CKD patients selected by purposive sampling. Data on fluid restriction compliance were collected using a validated questionnaire, while hypervolemia status was assessed by observation and body weight measurement. Data analysis used Spearman Rank correlation. Result: Among respondents, 63.3% were compliant with fluid restriction and 36.7% were non-compliant. Hypervolemia levels showed 40.8% mild, 28.6% moderate, and 30.6% severe. Statistical analysis found a significant negative correlation between fluid restriction compliance and hypervolemia occurrence (p=0.000; r=-0.756). Conclusion: There is a significant relationship between compliance with fluid restriction and hypervolemia among CKD patients undergoing hemodialysis. Increasing patient compliance is important to prevent complications. More specific and targeted treatment.